Impact of nurse-led self-management education on type 2 diabetes: a meta-analysis - Jiabao Sun; Zhenwei Fan; Mengyuan Kou; Xuewei Wang; Zhongmin Yue; Min Zhang (Frontiers in Public Health)
BackgroundDiabetes Self-Management Education (DSME) is a cornerstone strategy for improving glycemic control, yet its clinical effectiveness is often limited by suboptimal adherence. The aim of this study is to evaluate through meta-analysis the impact of nurse-led DSME on glycemic control, lipid profiles, and self-efficacy in adults with type 2 diabetes mellitus (T2DM).MethodsFollowing PRISMA 2020 guidelines, we systematically searched PubMed, EMBASE, and Web of Science databases (up to February 28, 2025). Inclusion criteria comprised: randomized controlled trials (RCTs) comparing nurse-led DSME (≥3 structured sessions) vs. usual care or other non-nurse-led interventions. Risk of bias was assessed using Cochrane RoB 2.0. Effect sizes [mean difference (MD) or standardized mean difference (SMD)] were pooled using R meta package with random-effects models (I2 > 50%). Subgroup analyses and meta-regression were performed.ResultsEight RCTs (reporting HbA1c outcomes) were included. Meta-analysis demonstrated: (1) Glycemic control: nurse-led DSME significantly reduced HbA1c at 4–6 months (MD = −0.92, 95% CI: −1.44 to −0.41) and >6 months (MD = −0.54, 95% CI: −0.86 to −0.23; p < 0.05), but not at 0–3 months (MD = −0.22, 95% CI: −1.15 to 0.51). Fasting blood glucose (FBG) showed significant improvement (MD = −0.20, 95% CI: −0.36 to −0.03). (2) Self-efficacy: the intervention group demonstrated significantly enhanced self-efficacy (SMD = 1.48, 95% CI: 1.04–1.92). (3) Lipid profiles: high-density lipoprotein (HDL) increased significantly (MD = 0.27, 95% CI: 0.14–0.41), while total cholesterol (TC), triglycerides (TG), and low-density lipoprotein (LDL) showed no significant changes. (4) Considerable heterogeneity was observed (HbA1c: I2 = 87.8%; self-efficacy: I2 = 84.5%). Meta-regression suggested borderline significant influence of follow-up duration on effect size (p = 0.059). No significant publication bias was detected (Egger's test p = 0.116).ConclusionNurse-led DSME effectively improves long-term glycemic control and self-efficacy while elevating HDL levels in T2DM patients, though standardization of intervention protocols is needed to reduce heterogeneity. This study supports integrating nurse-led models into diabetes management guidelines and recommends future research focus on long-term follow-up and cost-effectiveness analyses.Systematic review registrationhttps://doi.org/10.37766/inplasy2025.7.0114, identifier: NPLASY202570114.